The Effect of Compensation, Work Discipline, and Job Satisfaction on Non- Civil Servant Employees Work Productivity - Dyah Retno Hertanti; Sunardi Sunardi; Umu Khouroh (Social Science Academic, 2026)
Work productivity is an important indicator in assessing workforce performance, including non-civil servant employees (Non-ASN) who play a strategic role in supporting the implementation of government institutional functions. This study aims to analyze the effect of compensation, work discipline, and job satisfaction on the work productivity of Non-ASN employees at the Public Works and Spatial Planning Office (PUPR) of Madiun City, both partially and simultaneously. This research employs a quantitative approach with an associative causal research design. The research population consists of all Non-ASN employees at the PUPR Office of Madiun City, totaling 162 individuals, with a sample of 115 respondents determined using the Slovin formula. Research data will be collected through questionnaires using a Likert scale and analyzed using multiple linear regression analysis with the assistance of SPSS software. Based on theoretical frameworks and previous empirical studies, this research proposes the hypothesis that compensation, work discipline, and job satisfaction are expected to influence the work productivity of Non-ASN employees. This study is expected to contribute theoretically to the development of human resource management studies in the public sector and practically serve as a reference for the PUPR Office of Madiun City in formulating policies to improve the productivity of Non-ASN employees